2020
DOI: 10.1177/1753193420967527
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of congenital hand and upper limb differences on children: a qualitative study

Abstract: This qualitative study explored the psychosocial concerns of children born with congenital hand and upper limb differences (CHULDs) from the point of view of these children and their parents. Qualitative, in-depth, semi-structured interviews were conducted face-to-face with eight parent–child dyads. Open format questions allowed spontaneous emergence of relevant themes, followed by guided questioning. Thematic analysis of audio-recorded and transcribed interviews found that children as young as 5 years old had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
(37 reference statements)
3
13
0
Order By: Relevance
“…Nails are perceived as essential for the normal appearance of fingers, while nails in the wrong places seem to negatively impact appearance, which could be why a hand with nubbins and nails was perceived as cosmetically less pleasing than a nearly identical hand without nails. The results of this study further strengthen earlier findings that the thumb does not affect appearance more than any other finger, and that the total number of normal-appearing digits matters (Nietosvaara et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nails are perceived as essential for the normal appearance of fingers, while nails in the wrong places seem to negatively impact appearance, which could be why a hand with nubbins and nails was perceived as cosmetically less pleasing than a nearly identical hand without nails. The results of this study further strengthen earlier findings that the thumb does not affect appearance more than any other finger, and that the total number of normal-appearing digits matters (Nietosvaara et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The results of Bellew et al (2011) were based on parent and patient reports, which do not necessarily reflect the general population's viewpoints. Other studies have reported differences in results reported by caregivers compared with laypeople and care providers, with the former often giving better scores (Gkantidis et al, 2013;Goldfarb et al, 2007;Nietosvaara et al, 2021). In this study, we found the answers of caregivers and patients consistent with those of the other participants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The standardised approach to collecting data ensures its high quality and usefulness. It has been important to have regular engagement with AHDR registrants through newsletters providing aggregated data and requests for additional participation in research 23 . For the successful running and sustainability of such a register, consumer input into research ideas and feedback on results obtained is important.…”
Section: Discussionmentioning
confidence: 99%